Problems of elicitation and analysis of requirements to the program module of monitoring on the basis of the conditions of cognitive analysis - Kozulia, Tatyana Vladimirovna; Sviridova, Alyona Sergeevna; Kozulia, Maria Mikhailovna (НТУ "ХПІ", 2019)
There are risks of obtaining result that does not answer a work purpose statement when developing the software product for new subject area. It is necessary to pay attention on requirements to the software for elimination of such risks. This article is considering questions about collection and analysis requirements to a program module of sea water areas environmental monitoring. Program system "НДС Эколог" for ensuring continuous observation of sea water areas condition is noted by complex structure, high labor intensity of processing, storage and manipulations of data due to their significant amount. The software of this system makes a large-scale program complex for monitoring researches automation. However, according to the preliminary analysis of functionality "НДС Эколог" on quality control of dolphins living environment is not sufficient and need additional module development. Thus, the further development of this monitoring system is associated with the problem of elicitation and analyzing the requirements for the program module for calculating the coastal zones water resources quality. Elicitation requirements to additional program module is carried out on the basis of the standard documentation analysis, business processes of monitoring researches according to program engineering provisions. Identified Requirements are need check on integrity and lack of contradictions in their pithiness for further documenting according to the internatio nal recommendations standard about development of requirements specifications to the software IEEE STD 830 1993. To solve the problems of information support and software for integrated monitoring, a matrix of requirements was formed and cognitive modeling was applied. The requirements dependency matrix represents a simple and effective method of contradictions and overlappings identification, in case of simple systems consideration. Cognitive modeling promotes better understanding a problem situation, identification of contradictions and qualitative system analysis. The purpose of modeling consists in formation and specification of a studied object functioning hypothesis which consists of separate subsystems and elements. In this case, the system of requirements should reflect the causal relationships of object elements under study.

При розробці програмного продукту для нової предметної області існують ризики отримання результату, що не відповідає меті технічного завдання. Для усунення таких ризиків необхідно звернути увагу на вимоги до програмного забезпечення (ПЗ). У даній роботі розглянуті питання збору та аналізу вимог до програмного модулю з екологічного моніторингу морських акваторій. Програмна система "НДС Еколог" для забезпечення безперервного спостереження за станом морських акваторій відзначається складною структурою, високою трудомісткістю обробки, зберігання і маніпулювання даних у зв'язку з їх значним обсягом. Програмне забезпечення цієї системи становить масштабний комплекс програм з автоматизації моніторингових досліджень. Однак, за попереднім аналізом функціональних можливостей ПЗ "НДС Еколог" з контролю якості середовища життєдіяльності дельфінів не є достатнім і потребує розробки додаткового модулю. Таким чином, подальший розвиток цієї моніторингової системи пов'язаний с задачею збору та аналізу вимог до програмного модулю з розрахунку якості водних ресурсів прибережних зон. Збір вимог до додаткового програмного модулю проводиться на основі аналізу нормативної документації, бізнес-процесів моніторингових досліджень у відповідності до положень програмної інженерії. Визначені вимоги потребують перевірки на цілісність і відсутність протиріч у їх змістовності для подальшого документування відповідно до міжнародного стандарту рекомендацій з розробки специфікацій вимог до програмного забезпечення IEEE Std 830-1993. Для розв'язання задач інформаційного та програмного забезпечення у комплексному моніторингу було сформовано матрицю залежності вимог та застосовано когнітивне моделювання. Матриця залежності вимог являє собою простий та ефективний метод виявлення протиріч і перекрить, у випадку розгляду нескладних систем. Когнітивне моделювання сприяє кращому розумінню проблемної ситуації, виявленню суперечностей та якісному аналізу системи. Мета моделювання полягає в формуванні та уточненні гіпотези про функціонування досліджуваного об'єкта, який складається з окремих підсистем та елементів. У такому разі система вимог повинна відображати причинно-наслідкові зв'язки елементів досліджуваного об'єкта.
Задачі збору та аналізу вимог до програмного модулю з моніторингу на основі положень когнітивного аналізу
Keywords: software module; dependency matrix; cognitive modeling; environmental monitoring; матриця залежності; когнітивне моделювання; екологічний моніторинг